2012
DOI: 10.1007/s11302-012-9337-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-synonymous polymorphisms in the P2RX 4 are related to bone mineral density and osteoporosis risk in a cohort of Dutch fracture patients

Abstract: In the present study we investigated whether single nucleotide polymorphisms (SNPs) in the P2RX 4 , which alter the P2X 4 R function, are associated with the development of osteoporosis and whether an interaction between the P2X 4 R and P2X 7 R confer a synergistic effect of these two receptors on osteoporosis risk. Patients with fracture (690 females and 231 males, aged ≥50 years) were genotyped for three non-synonymous P2X 4 R SNPs. Bone mineral density (BMD) was measured at the total hip, lumbar spine, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…P2X5R may be a therapeutic target for treatment for inflammatory bone loss ( Kim et al, 2017 ). Polymorphisms in the P2X4 and P2X7R genes ( Husted et al, 2013 ) and the Leu46Pro polymorphism of the human P2Y 2 R gene were linked to bone mineral density and the risk of osteoporosis in Dutch fracture patients ( Wesselius et al, 2013 ). It was suggested that clopidogrel, a P2Y 12 R antagonist used for stroke and thrombosis, increases the risk of fractures in osteoporotic patients ( Jørgensen et al, 2012 ).…”
Section: Musculoskeletal Diseasesmentioning
confidence: 99%
“…P2X5R may be a therapeutic target for treatment for inflammatory bone loss ( Kim et al, 2017 ). Polymorphisms in the P2X4 and P2X7R genes ( Husted et al, 2013 ) and the Leu46Pro polymorphism of the human P2Y 2 R gene were linked to bone mineral density and the risk of osteoporosis in Dutch fracture patients ( Wesselius et al, 2013 ). It was suggested that clopidogrel, a P2Y 12 R antagonist used for stroke and thrombosis, increases the risk of fractures in osteoporotic patients ( Jørgensen et al, 2012 ).…”
Section: Musculoskeletal Diseasesmentioning
confidence: 99%
“…Loss of function polymorphisms in the P2X7 receptor have been associated with increased fracture risk, reduced BMD and osteoporosis Husted et al, 2013;Ohlendorff et al, 2007). Recently, it was reported that a single SNP in the P2X4 receptor gene (tyrosine to cysteine at position 315) is associated with an increased risk of osteoporosis and lower lumbar spine BMD (Wesselius et al, 2013b).…”
Section: P2 Receptor Polymorphisms and Bonementioning
confidence: 99%
“…P2X 4 receptor plays an integral part of calcium‐dependent intracellular processes via membrane depolarization. These receptors have been implicated in a variety of functions including apoptosis, strengthening synaptic connections in hippocampal neurons, seizures, epilepsy, amyotrophic lateral sclerosis, and regulation of bone mass (Solini et al, ; Baxter et al, ; Wesselius et al, ; Engel et al, ; Volonté et al, ). Even though this receptor plays several physiological roles, research has focused on its function in regards to the heart, neuropathic pain, and lysosomal fusion.…”
Section: Function and Location Of P2x Receptorsmentioning
confidence: 99%